2020
DOI: 10.1200/cci.20.00077
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Tumor Immune Microenvironment Identifies M0 Macrophage-Enriched Cluster as a Poor Prognostic Factor in Hepatocellular Carcinoma

Abstract: PURPOSE Hepatocellular carcinoma (HCC) is characterized by a poor prognosis and a high recurrence rate. The tumor immune microenvironment in HCC has been characterized as shifted toward immunosuppression. We conducted a genomic data-driven classification of immune microenvironment HCC subtypes. In addition, we demonstrated their prognostic value and suggested a potential therapeutic targeting strategy. METHODS RNA sequencing data from The Cancer Genome Atlas–Liver Hepatocellular Carcinoma was used (n = 366). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 53 publications
6
37
0
Order By: Relevance
“…CD8 + T cells are involved in the killing of tumor cells (Sasidharan Nair and Elkord, 2018). Increased M0 macrophage composition is associated with a poorer prognosis in patients with cancer (Farha et al, 2020;Jairath et al, 2020). These data indicated that LUAD with high expression of LRMP may have a higher level of anti-tumor immune cell infiltration and a more positive tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…CD8 + T cells are involved in the killing of tumor cells (Sasidharan Nair and Elkord, 2018). Increased M0 macrophage composition is associated with a poorer prognosis in patients with cancer (Farha et al, 2020;Jairath et al, 2020). These data indicated that LUAD with high expression of LRMP may have a higher level of anti-tumor immune cell infiltration and a more positive tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…While the enrichment of unpolarized M0 macrophages in the tumor microenvironment has been demonstrated to be detrimental for survival of patients with hepatocellular carcinoma and sarcoma 16,40 , their role in MDS and other hematologic malignancies has been scarcely reported.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to outperform other methods in estimating the relative proportion of closely related cell types in bulk tumors without physical cell sorting 12,13 . While the utility of CIBERSORT and CIBERSORTx has been validated in multiple tumor types [14][15][16][17] , their applicability in hematological malignancies remains scarce. A study demonstrated higher fraction of M2 macrophage as a predictor of inferior event-free survival (EFS) and overall survival (OS) in patients with acute myeloid leukemia (AML), and identified the macrophage marker CD206 as a novel prognostic indicator in these patients 18 .…”
Section: Newman Et Al Recently Developed a Computational Method Cibersort (Cell Type Identification Bymentioning
confidence: 99%
“…Treg infiltration is associated with poor prognosis of BLCA [62,63]. M0 macrophages are related to poor prognosis of HCC [64]. M2 macrophages are involved in tumor microangiogenesis in BLCA and are related to tumor stage and invasiveness [65].…”
Section: Discussionmentioning
confidence: 99%